2k-24=4k

Simple and best practice solution for 2k-24=4k equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2k-24=4k equation:


Simplifying
2k + -24 = 4k

Reorder the terms:
-24 + 2k = 4k

Solving
-24 + 2k = 4k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-4k' to each side of the equation.
-24 + 2k + -4k = 4k + -4k

Combine like terms: 2k + -4k = -2k
-24 + -2k = 4k + -4k

Combine like terms: 4k + -4k = 0
-24 + -2k = 0

Add '24' to each side of the equation.
-24 + 24 + -2k = 0 + 24

Combine like terms: -24 + 24 = 0
0 + -2k = 0 + 24
-2k = 0 + 24

Combine like terms: 0 + 24 = 24
-2k = 24

Divide each side by '-2'.
k = -12

Simplifying
k = -12

See similar equations:

| f(x)=6x^2+41x-7 | | 24-6b=2b | | g(n)=-2n+2 | | 3x+2=11x-1 | | k^2+3k-90= | | 4(2x+8)+2(2x+3)=182 | | -44-16x=-19x+4 | | 2a/3-1/2=5/6 | | (88*1)+13= | | 3-f=5/6 | | 7(5x+1)=147 | | 6x+2=-6x+15 | | 5x+3y=8.25 | | 3z+2t[-5z]+6= | | X+x(.18)=1500 | | 2x-3y+5z=.3 | | f(x)=x^5-3x^3-10x | | 2(3x+1)=-3(2x-5) | | x+-8=7 | | 20=-3w-5w-27 | | 5/15=3/v | | 9k^2+12k+4=20 | | -5(1-8p)-7=-292 | | 2s+[-4s]= | | 2/3(-15-4) | | 9/5=n/12 | | 16x+10=-3 | | 8a-8=28+6a | | 1/2* | | 6p+22=19 | | 6(3x-4)=-168 | | -7(1-5x)=-182 |

Equations solver categories